Proceedings of the 39th Annual Hawaii International Conference on System Sciences (HICSS'06) 2006
DOI: 10.1109/hicss.2006.534
|View full text |Cite
|
Sign up to set email alerts
|

When Online Reviews Meet Hyperdifferentiation: A Study of Craft Beer Industry

Abstract: We analyze how online reviews are used to evaluate the effectiveness of product differentiation strategies based on the theories of hyperdifferentiation and resonance marketing. Hyperdifferentiation says that firms can now produce almost anything that appeals to consumers and they can manage the complexity of the increasingly diverse product portfolios that result. Resonance marketing says that informed consumers will purchase products that they actually truly want. When consumers become more informed, firms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 16 publications
5
112
2
3
Order By: Relevance
“…Willemsen, Neijens, Bronner, and de Ridder (2011) defined those ratings as numeric summary statistics (overall ratings) shown in the form of five-point star recommendations at the surface level of the review and reviewers' general assessments of the product. The extant literature has demonstrated an association between online review ratings and customer behaviours (Clemons et al, 2006;Park, Lee, & Han, 2007). The findings of previous studies can be presented in relation to two different arguments.…”
Section: Review Star Ratingsmentioning
confidence: 92%
See 1 more Smart Citation
“…Willemsen, Neijens, Bronner, and de Ridder (2011) defined those ratings as numeric summary statistics (overall ratings) shown in the form of five-point star recommendations at the surface level of the review and reviewers' general assessments of the product. The extant literature has demonstrated an association between online review ratings and customer behaviours (Clemons et al, 2006;Park, Lee, & Han, 2007). The findings of previous studies can be presented in relation to two different arguments.…”
Section: Review Star Ratingsmentioning
confidence: 92%
“…They also identified that the valence (average numerical rating) (Dellarocas, Zhang & Awad, 2007) and number of online consumer reviews (Duan et al, 2008) are vital predictors of box office sales. Clemons, Gao, and Hitt (2006) showed that not only the variance of ratings but also the strength of the most positive quartile of reviews has a significant impact on the growth of craft beers. In addition to the features of online reviews, the effect of the degree to which review writers disclose their identity in the evaluation of product quality and product sales has been discussed (e.g., Forman, et al, 2008).…”
Section: Online Consumer Reviewsmentioning
confidence: 99%
“…The development of Internet marketplaces where consumers can establish interaction has undoubtedly has affected the way a review -as an expression of prior experience-influences the way consumers make a choice about a product or a service based on prior experiences [6,7]. First and foremost, the use of online mechanisms for the reporting and categorization of reviews by a product or a service in conjunction with the development of modern search engines has eliminated the search costs for the consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the literature specifically devoted to online feedback systems in a variety of virtual contexts has focused on explaining the impact that ratings have on promoting a variety of outcomes such as price premiums and trust in electronic commerce environments (Ba & Pavlou, 2002;Chevalier & Mayzlin, 2006;Clemons, Gao, & Hitt, 2006;Dellarocas, 2006;Pavlou & Dimoka, 2006;Son et al, 2006), consumer purchase errors (Godes & Silva, 2012), decision quality and time (Poston & Speier, 2005), and effort to contribute content in user-generated content websites (Chen et al, 2011). Unfortunately, this prior literature has reported mixed empirical results whereby sometimes the impact of ratings is positive, negative, or not significant (Ba & Pavlou, 2002;Ghose et al, 2006;Kauffman & Wood, 2005).…”
Section: Online Ratingsmentioning
confidence: 99%